Deciphering preferential interactions within supramolecular protein complexes: the proteasome case. Issue 1 (5th January 2015) - Fabre, Bertrand; Lambour, Thomas; Garrigues, Luc; Amalric, François; Vigneron, Nathalie; Menneteau, Thomas; Stella, Alexandre; Monsarrat, Bernard; Van den Eynde, Benoît; Burlet‐Schiltz, Odile; Bousquet‐Dubouch, Marie‐Pierre
Abstract : A new approach for analyzing sub‐complex composition by combining affinity purification and protein abundance correlation profiling by mass spectrometry is employed to characterize the dynamic and heterogeneous nature of human proteasome complexes. Abstract: In eukaryotic cells, intracellular protein breakdown is mainly performed by the ubiquitin–proteasome system. Proteasomes are supramolecular protein complexes formed by the association of multiple sub‐complexes and interacting proteins. Therefore, they exhibit a very high heterogeneity whose function is still not well understood. Here, using a newly developed method based on the combination of affinity purification and protein correlation profiling associated with high‐resolution mass spectrometry, we comprehensively characterized proteasome heterogeneity and identified previously unknown preferential associations within proteasome sub‐complexes. In particular, we showed for the first time that the two main proteasome subtypes, standard proteasome and immunoproteasome, interact with a different subset of important regulators. This trend was observed in very diverse human cell types and was confirmed by changing the relative proportions of both 20S proteasome forms using interferon‐γ. The new method developed here constitutes an innovative and powerful strategy that could be broadly applied for unraveling the dynamic and heterogeneous nature of other biologically relevant supramolecular protein complexes. Synopsis: A new approach for analyzing sub‐complex composition by combining affinity purification and protein abundance correlation profiling by mass spectrometry is employed to characterize the dynamic and heterogeneous nature of human proteasome complexes. This novel strategy allows in‐depth characterization of proteasome complexes and confident identification of specific protein interactions. Previously unknown preferential associations between proteasome sub‐complexes are revealed and strongly suggest that interactions within proteasome particles do not occur randomly. The standard proteasome and immunoproteasome, two main 20S proteasome subtypes, preferentially associate with different subsets of proteins regulating their activities. In vivo modulation of 20S catalytic subunits using IFNγ stimulation confirms PA28αβ and PA200/PI31 as specific regulators of 20S immunoproteasome and 20S standard proteasome, respectively.